A Collaborative Approach to Planning - Julie Davis; Alison Scholl (Universitas Diponegoro, 2021)
To reflect Trent University’s academic leadership in environmental and indigenous studies, Trent has undertaken a collaborative campus stewardship and land-use planning process that prioritizes collection of Indigenous Traditional Knowledge (ITK) and engagement with the local First Nations. Trent’s Symons campus is rich in natural and cultural assets, with drumlins, wetlands, woodlands, meadows and farmland, and diverse flora and fauna. A primary goal of the campus plan is to conserve biological diversity, maintain ecological functions, and sustain ecosystem services across more than 560 hectares, whilst enabling campus expansion and joint benefit infrastructure projects to move forward efficiently and effectively. Trent’s experience in bringing ITK to the forefront of campus stewardship and land-use planning warrants critical examination to advance promising practices for conservation of biodiversity through a collaborative approach to planning